2004
DOI: 10.1111/j.1432-1033.2004.04379.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the basic helix‐loop‐helix transcription factor DEC1 in circadian regulation

Abstract: The basic helix-loop-helix transcription factor DEC1 is expressed in a circadian manner in the suprachiasmatic nucleus where it seems to play a role in regulating the mammalian circadian rhythm by suppressing the CLOCK/BMAL1-activated promoter. The interaction of DEC1 with BMAL1 has been suggested as one of the molecular mechanisms of the suppression [Honma, S., Kawamoto, T., Takagi, Y., Fujimoto, K., Sato, F., Noshiro, M., Kato, Y. & Honma, K. (2002) Nature 419, 841-844]. Deletion analysis of DEC1 demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 32 publications
(55 reference statements)
7
113
0
Order By: Relevance
“…Mutation analysis demonstrated that the basic region in DEC2 essential for the suppressive activity coincided with the region in DEC1 as described previously (10). The amino acid residue, 57 Arg, in the basic region of DEC2 is conserved among the group B bHLH proteins, including USF, c-Myc, MAX and MAD (16), which can bind to the CACGTG E-box (9,17) and some other transcription factors (6,18).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Mutation analysis demonstrated that the basic region in DEC2 essential for the suppressive activity coincided with the region in DEC1 as described previously (10). The amino acid residue, 57 Arg, in the basic region of DEC2 is conserved among the group B bHLH proteins, including USF, c-Myc, MAX and MAD (16), which can bind to the CACGTG E-box (9,17) and some other transcription factors (6,18).…”
Section: Discussionsupporting
confidence: 69%
“…We recently demonstrated that Dec2 (Sharp-1) and Dec1 (Sharp-2/Stra13/ Clast5) were new regulators of the mammalian molecular clock which caused CLOCK/BMAL1-mediated transactivation (6). DEC2 and DEC1 are basic helix-loop-helix (bHLH) transcription factors (7,8) which bind to CACGTG E-boxes and BMAL1 to suppress transcription from target genes (6,9,10). The expression of DEC2 and DEC1 shows circadian rhythms in most organs, including the SCN (6,12), and the phases of the circadian rhythms for Dec2 and Dec1 were similar to those for Per1, Per2, Per3 (13), Rev-Erb · (14) and were somewhat similar to Cry1 (15).…”
Section: Introductionmentioning
confidence: 99%
“…As histone deacetylase (HDAC)-dependent mechanisms had been previously suggested (Sun and Taneja, 2000), trichostatin A (TSA) treatments remarkably canceled the repression of MLH1 promoter activity by DEC in a treatment dose-dependent manner without any detectable cytotoxicity (Figure 2d). Moreover, mutant type of DEC1 which had DNA-binding domain but lacked most of functional domains (Li et al, 2003;Sato et al, 2004) failed to repress MLH1 promoter activities, even enhanced them, suggesting that just a competitive occupancy on the promoter was not sufficient to explain the repression (Figure 2e). …”
Section: Mlh1 Expression At Both Protein and Mrna Levels Under Hypoximentioning
confidence: 99%
“…Base-exchanged mutants of putative E-box sites in pGL-MLH1 Pro0.27 were generated by PCR-based sitedirected mutagenesis as previously reported (Tanimoto et al, 2003). Details of expression plasmid vectors of DEC1 (pcDNA-DEC1, p3xFLAG-CMV-DEC1 or pcDNA-DEC1 1-139) and DEC2 (pcDNA-DEC2) were previously described Sato et al, 2004). pcDNA-FLAG-DEC2 was constructed by swapping DEC2 cDNA fragment of pcDNA-DEC2 with the pcDNA-FLAG (kindly provided by Dr Igarashi).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…The transcription factor DEC2 also plays an important role in the circadian rhythm (20). Previous studies showed a rhythmic expression of DEC1 and DEC2 mRNA in the suprachiasmatic nucleus, and peripheral tissues (21)(22)(23)(24)(25). DEC1 and were harvested and sub-cultured.…”
Section: Introductionmentioning
confidence: 99%